A study of GaN nucleation and coalescence in the initial growth stages on nanoscale patterned sapphire substrates via MOCVD. Issue 42 (12th October 2018) - Chen, Yifan; Chen, Zhizhong; Li, Junze; Chen, Yiyong; Li, Chengcheng; Zhan, Jinglin; Yu, Tongjun; Kang, Xiangning; Jiao, Fei; Li, Shunfeng; Zhang, Guoyi; Shen, Bo
Abstract : A study of GaN nucleation and coalescence behaviors in the initial growth stages on nanoscale patterned sapphire substrates (NPSS) is presented. Abstract : GaN growth on cone-shaped nanoscale patterned sapphire substrates (NPSS) in the initial stages was investigated via a series of growth interruptions. The thickness of the nucleation layer (NL) was optimized as 15 nm. A high-quality GaN film was achieved with an average surface roughness of 0.13 nm over 5 × 5 μm 2, a threading dislocation density (TDD) of 1.80 × 10 8 cm −2 and a residual stress of 0.40 GPa. X-ray diffraction (XRD) ω / φ -scans, cathodoluminescence (CL) mapping and transmission electron microscopy (TEM) measurements were carried out to study the GaN coalescence process on NPSS. Nano-nucleating, lateral growth and the submerging of the large tilt grains were confirmed as the primary factors that reduced the TDD and residual stress. The mechanism for GaN nucleation on NPSS and its effect on the subsequent growth stages were elucidated.